Diagnostic value of ultrasound in children with transverse testicular ectopia - Wei Zhou; Wei Zhou; Shoulin Li; Hao Wang; Hao Wang; Jianchun Yin; Xiaodong Liu; Junhai Jiang; Guanglun Zhou; Jianguo Wen (Frontiers Media S.A., 2022)
ObjectiveThe study aimed to investigate the diagnostic value of ultrasound in children's transverse testicular ectopia (TTE).Materials and methodsWe retrospectively studies all TTE cases diagnosed in our hospital from January 2017 to December 2021. All cases were evaluated by ultrasound examination and compared to physical examination and diagnostic laparoscopy results.ResultsThis study included 14 TTE patients in total, with a median age was 1.08 years. In the 14 TTE, physical examination found 10 TTE cases, of which nine testes were located in the opposite scrotum, one testis was located in the opposite groin, and the other four testes were not observed by physical examination. All cases were diagnosed by preoperative ultrasound, and nine testes were located in the opposite scrotum, two testes were located in the opposite groin, and three testes were located next to the opposite iliac vessel in the abdominal cavity. Preoperative ultrasound showed the ectopic spermatic cord in six cases (6/14, 42.8%) and persistent Müllerian duct syndrome (PMDS) in one case (1/14, 7%). Diagnostic laparoscopy finally confirmed 14 cases of TTE, which was consistent with preoperative ultrasound, and the coincidence rate was 100% (14/14). Among the 14 cases of TTE, diagnostic laparoscopy showed that 12 cases had ectopic spermatic vessels and vas deferens (12/14, 85.7%), and six cases were associated with PMDS (6/14, 42.8%). When TTE was associated with the ectopic spermatic cord and PMDS, the diagnostic performance of diagnostic laparoscopy was better than that of preoperative ultrasound (P < 0.05). The testis volume of the affected side of TTE was less than that of the contralateral testis (P < 0.05).ConclusionUltrasonography is very helpful for the preoperative diagnosis of TTE in children, and it is suitable as a non-surgical method for locating ectopictestis. Preoperative assessment of the exact presence of PMDS is difficult and unclear. This may be related to factors such as pelvic developmental stages in infancy, examination techniques, and atypical imaging findings of PMDS.